2020
DOI: 10.28940/terra.v38i3.737
|View full text |Cite
|
Sign up to set email alerts
|

Respuesta agronómica del chile dulce (Capsicum annuum L.) a la aplicación de Bacillus subtilis y lombricomposta en invernadero

Abstract: El uso de agroquímicos en el cultivo de chile dulce ha originado la búsqueda de alternativas de fertilización como Bacillus subtilis y lombricomposta, los cuales, son una opción para producir alimentos sin afectar al ambiente, salud humana y animal. El objetivo de este estudio fue evaluar el efecto de la incorporación individual y en conjunto de B. subtilis y lombricomposta sobre la respuesta agronómica de chile dulce bajo invernadero. Se utilizó un diseño completamente al azar con 15 repeticiones por cada tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…On the other hand, regardless of the irrigation level, the inoculation of plants with Bacillus subtilis promoted an increase of 13% in the leaf area index and 12% in the N content of the leaves compared to the treatment without the inoculation. B. subtilis also increased the leaf area in sweet peppers [43] and leaf N content in sugarcane [44]. Aquino [45] observed that five strains of B. subtilis increased the foliar N content in corn crops compared to uninoculated plants.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, regardless of the irrigation level, the inoculation of plants with Bacillus subtilis promoted an increase of 13% in the leaf area index and 12% in the N content of the leaves compared to the treatment without the inoculation. B. subtilis also increased the leaf area in sweet peppers [43] and leaf N content in sugarcane [44]. Aquino [45] observed that five strains of B. subtilis increased the foliar N content in corn crops compared to uninoculated plants.…”
Section: Discussionmentioning
confidence: 95%
“…In another article [11], presents the results of testing both vermicompost and B. subtilis when growing pepper (Capsicum annuum L.) in greenhouse conditions. The effectiveness of the use of fertilizers was assessed by studying such growth parameters as the height and diameter of the stem, leaf area, budding phase and yield of pepper fruits.…”
Section: Discussionmentioning
confidence: 99%
“…An example of this is vermicomposting, which is the process by which organic waste is decomposed through the synergic actions of earthworms and microbial communities [7], in addition to containing nutrients that are important in the growth and productivity of plants [8], and also substantially improve the chemical, biological and physical properties of the soil [9]. Therefore, the application of vermicompost can represent an alternative to help modify the management of agricultural inputs, promoting growth, productivity and profitability of the crops in a sustainable manner [10]. Because of the aforementioned, this study sets out to understand the agronomic response of two experimental varieties of habanero chili peppers identified as HNC-6 and HCC-8 to the application of band vermicomposting.…”
Section: Introductionmentioning
confidence: 99%